Urban development and architecture in mountainous areas using the example of the highest settlements in the Andean region of South America - Orel Daria A.; Tseluiko Dmitry S. (Архитектон, 2025)
The article examines the architectural and planning features of the most historically and industrially significant cities in South America at record-breaking altitudes relative to sea level. The emergence, development and cultural identity of these cities in modern times are studied. The historical contexts of their origin and development are revealed. The plans of these cities and their adaptation to mountainous terrains and climate are overviewed. A comparative analysis is carried out in relation to the historical period under consideration. In addition to the urban development structure, the features of the colonial architectural style and the specifics of national identity are highlighted. In conclusion, a comparative analysis of the chronological stages of highland city development in South America is made.